Pain and quality of life of adolescents with primary dysmenorrhea in Tbilisi, Georgia, 2008. Cross sectional study - Tinatin Gagua; Tkeshelashvili Besarion; David Gagua (Federación Colombiana de Obstetricia y Ginecología, 2013)
Objective: The study aimed to measure the effect of primary dysmenorrhea on the quality of life of female adolescents living in Tbilisi, Georgia, and to compare Quality of Life (QoL) with healthy controls. Materials and methods: Cross-sectional study of 424 women aged 14-20, living in Tbilisi, Georgia, coming from academic and research institutions. The women were divided into those suffering dysmenorrhea (exposure group) and those without pain (control group). Reproductive history, demographic features, menstrual pattern, severity of dysmenorrhea and quality of life using the generic instrument EQ-5D, were measured. The Independent T student test was used for group comparison. Results: The group with dysmenorrhea (276) showed a lower Quality of Life score of 0.69 ± 0.20 vs. 0.94 ± 0.10 in the control group (p = 0.000); the Quality of Life VAS was also lower at 74.38 ± 17.83 vs. 87.02 ± 12.03 (p = 0.000). Of the subjetcs with primary dismenorrhea, 56.6% reported school absenteeism due to pain. Conclusion: Primary dysmenorrhea is a common problem in the adolescent population of Tbilisi, Georgia. The results of this study demonstrate that adolescents with primary dysmenorrhea in Georgia experience significantly lower physical and psychosocial health-related QoL than their healthy peers.